2021
DOI: 10.1111/jgs.17153
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity of the BNT162b2 vaccine in frail or disabled nursing home residents: COVID‐A study

Abstract: Background/Objectives The safety and immunogenicity of the BNT162b2 coronavirus disease 2019 (COVID‐19) vaccine in older adults with different frailty and disability profiles have not been well determined. Our objective was to analyze immunogenicity of the BNT162b2 mRNA COVID‐19 vaccine in older adults across frailty and disability profiles. Design Multicenter longitudinal cohort study. Setting and participants A total of 134 residents aged ≥65 years with different frailty and disability profiles in five long‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
62
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(73 citation statements)
references
References 23 publications
11
62
0
Order By: Relevance
“…It seems now almost indisputable that universal COVID-19 vaccination will be the keystone in all strategies aimed at stopping or limiting the worldwide circulation of SARS-CoV-2. Nonetheless, although the efficacy of most currently licensed vaccines appears considerably high, especially at reducing the risk of clinical deterioration [15], a considerable inter-individual heterogeneity in post-vaccine immune response is being increasingly noted in some specific populations, especially in the elderly [16] and in immunosuppressed patients [17,18]. Unfortunately, low vaccine responders mostly include categories of frail patients, who already have a magnified risk of unfavorable disease progression if contracting SARS-CoV-2 [19].…”
Section: Discussionmentioning
confidence: 99%
“…It seems now almost indisputable that universal COVID-19 vaccination will be the keystone in all strategies aimed at stopping or limiting the worldwide circulation of SARS-CoV-2. Nonetheless, although the efficacy of most currently licensed vaccines appears considerably high, especially at reducing the risk of clinical deterioration [15], a considerable inter-individual heterogeneity in post-vaccine immune response is being increasingly noted in some specific populations, especially in the elderly [16] and in immunosuppressed patients [17,18]. Unfortunately, low vaccine responders mostly include categories of frail patients, who already have a magnified risk of unfavorable disease progression if contracting SARS-CoV-2 [19].…”
Section: Discussionmentioning
confidence: 99%
“…Several papers addressed the efficacy of different SARS-CoV-2 vaccines either through Phase II and III of clinical trials [18][19][20] or field investigations [9][10][11]. Few of them detailed data regarding elderly and persons living in nurse facility [12][13][14][15] and outbreaks after the first and second dose were reported [21][22][23]. At present, cohorts <16 years or >80 years who might show reduced vaccine reactiveness are limited.…”
Section: Discussionmentioning
confidence: 99%
“…Several reports indicate that vaccination of old age is showing to protect from severe disease, and risk of death by conferring a degree of humoral immunity [9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…However, the efficacy of these human vaccines in these patients is questionable [ 173 ]. The BNT162b2 vaccine was shown to be effective and safe in a study of 134 patients and older adults with various frailty and disability profiles, providing protection regardless of their condition [ 174 ]. On the other hand, several studies have found lower levels of antibodies in patients with multiple myeloma after the first dose of this vaccine than in the vaccine trials [ 175 , 176 ].…”
Section: Preventionmentioning
confidence: 99%